PERAN PENDAMPING LOKAL DESA (PLD) DALAM PERENCANAAN PEMBANGUNAN DESA: (Studi di Desa Tirtomoyo Kecamatan Pakis Kabupaten Malang) - Roro Ayu Estiningtyas (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Various efforts have been made by the central and regional governments in an effort to empower villages, one of which is through the formation of village assistants. implementation of Law no. 6 of 2014 concerning Villages, systematically and sustainably implement empowerment through facilitation, supervision, and assistance. The purpose of this study was to determine and analyze the role and contribution of local village facilitators in the development planning of Tirtomoyo village, Pakis district, Malang regency. The results of the study indicate that (a) The local village assistant plays a role as a facilitator in the process of gathering the aspirations of the village community; (b) Intermediary mediator of public relations with the village government; (c) Experts in providing information and providing advice on village development, especially in planning and budgeting; (d) Social Planners in helping to solve social problems; (e) Representing Community Groups in need of assistance, ensuring that the community gets their rights in obtaining public services; (f) Business activists in reducing inequality and optimizing equality. On the other hand, the optimization of the role of village facilitators still needs to be improved, because local village facilitators have a bigger role in efforts to improve the standard of living of the community, so they carry out more empowerment activities that are directly related to the community.